2006
DOI: 10.1007/s10495-006-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 expression increases serum-withdrawal-induced apoptosis, mediated by re-distribution of Fas into lipid rafts, in stably transfected Swiss 3T3 cells

Abstract: To examine the function of syndecan-2, one of the most abundant heparan sulfate proteoglycans in fibroblasts, we obtained stably transfected Swiss 3T3 clones. We examined the effects of stable syndecan-2 overexpression on programmed cell death, finding that syndecan-2 transfected cells were more sensitive to apoptosis induced by serum-withdrawal than control cells. In addition, overexpression of syndecan-2 correlates with increased membrane levels of the Fas/CD95 receptor, suggesting that the increased serum-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Self-induction of syndecan-2 is consistent with previous data showing that apoptotic factors induce syndecan-2, whereas syndecan-2 drives the apoptotic response (8,12). Hence, on apoptotic stimulation, syndecan-2 expression may rapidly increase to adapt the normal cell response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Self-induction of syndecan-2 is consistent with previous data showing that apoptotic factors induce syndecan-2, whereas syndecan-2 drives the apoptotic response (8,12). Hence, on apoptotic stimulation, syndecan-2 expression may rapidly increase to adapt the normal cell response.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, alterations of mechanisms that control cell death contribute to resistance to chemotherapy. Syndecan-2, a membrane heparan sulfate proteoglycan, was shown to modulate events related to the apoptotic response, such as Fas distribution into lipid rafts in fibroblasts (8,9). We have previously shown that syndecan-2 controls the induction of apoptosis in osteoblasts, modulating mitogen-activated protein kinase and protein kinase Cδ signaling (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3B, the effect of brefeldin A on the translocation of Fas was probably due to the inhibition of secretion of HS proteoglycans (HSPGs) that contained the HS4C3-binding epitope. Recently, it has been demonstrated that Fas is redistributed from intracellular pools to lipid rafts on the cell surface in Swiss 3T3 cells overexpressing syndecan-2 [42]. However, the mechanism of this redistribution has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…(11)(12)(13)(14) Syndecan-2-dependent signaling contributes to the control of caspasedependent and independent cell death, and consistently, mediates the anti-oncogenic effects of chemotherapeutic drugs in OS cells. (13,15,16) We showed that the expression of syndecan-2 is low in OS cell lines and tissues compared to normal osteoblasts, (15) suggesting that decreased cell response to apoptotic stress and chemoresistance may be related to alterations of syndecan-2 expression. We also showed that low syndecan-2 expression in OS cells is due, in part, to the high repressive activity of the Wnt/b-catenin/T-cell factor (TCF) pathway.…”
Section: Introductionmentioning
confidence: 83%